2020
DOI: 10.1016/j.jns.2020.117137
|View full text |Cite
|
Sign up to set email alerts
|

Neurological correlates of brain reward circuitry linked to opioid use disorder (OUD): Do homo sapiens acquire or have a reward deficiency syndrome?

Abstract: The extant literature confirms that an array of polymorphic genes related to- neurotransmitters and second messengers govern the net release of dopamine in the Nucleus Accumbens (NAc) in the mesolimbic region of the brain. They are linked predominantly to motivation, anti-stress, incentive salience (wanting), and wellbeing. Notably, in 2000 the Nobel Prize was awarded to Carlsson, Greengard, and Kandel for their work on the molecular and cellular function of dopaminergic activity at neurons. This historical ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 170 publications
0
21
0
Order By: Relevance
“…This condition may be innate or acquired and is clinically manifested as anhedonia, numbing, apathy, or decreased motivation for natural reinforcers [ 324 , 325 ]. According to the hypothesis, opioid/endorphin deficiency increases a person’s vulnerability for OUD by disrupting interactions between midbrain opioid and DA neurotransmitter systems [ 326 ]. This has been supported by evidence that ELS alters µ- and k-receptor mRNA levels [ 62 , 63 , 64 ] and decreases downstream DA signaling [ 63 , 65 ] in a way that may alter the reinforcing and antinociceptive effects of opioids.…”
Section: Role Of Dopamine Neurotransmitter System In Els and Oudmentioning
confidence: 99%
“…This condition may be innate or acquired and is clinically manifested as anhedonia, numbing, apathy, or decreased motivation for natural reinforcers [ 324 , 325 ]. According to the hypothesis, opioid/endorphin deficiency increases a person’s vulnerability for OUD by disrupting interactions between midbrain opioid and DA neurotransmitter systems [ 326 ]. This has been supported by evidence that ELS alters µ- and k-receptor mRNA levels [ 62 , 63 , 64 ] and decreases downstream DA signaling [ 63 , 65 ] in a way that may alter the reinforcing and antinociceptive effects of opioids.…”
Section: Role Of Dopamine Neurotransmitter System In Els and Oudmentioning
confidence: 99%
“…Volkow has suggested that evidence-based prevention and treatment interventions can reduce overdose mortality by 40%. However, opioid use disorder (OUD) is a chronic relapsing disorder that, while initially driven by brain reward activation, increasingly engages anti-reward neurocircuits [20] that drive adverse emotional states and relapse [21].…”
Section: Transition With Urgency Overdose Reversal To Evaluation Diagnoses and Treat The Whole Patient With Oudmentioning
confidence: 99%
“…Discontinuation of MAT is associated with high rates of relapse and an increased risk of overdose. Relapsing patients are often given the same MAT treatments again and again and again [20]. The risk of overdose and relapse remains even after years of stable recovery.…”
Section: Transition With Urgency Overdose Reversal To Evaluation Diagnoses and Treat The Whole Patient With Oudmentioning
confidence: 99%
“…Neurologically, MATs may induce persistent changes that compromise endorphin, dopamine, and other brain systems. Long-term agonist treatments may be necessary for lack of other options, but we caution that data on long-term use vs. short-term harm reduction is lacking [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the current viral pandemic, there is also a profound, pre-existing, and growing worldwide epidemic of addiction to opioids, psychostimulants, alcohol, and cannabis. Treatments themselves, like long-term agonist treatments for opioid use disorder (OUD), may also cause Reward Deficiency Syndrome (RDS) [ 4 ], resulting in harm and deadly consequences that rival and might eclipse the magnitude of the current viral issue.…”
Section: Introductionmentioning
confidence: 99%